Evaluation of demographical, etiological and clinical characteristics of acute drug poisoning - Begum, RA; Afrin, T; Forhad, AJ; Khatun, SA (Journal of Dhaka National Medical College & Hospital, 2019)
Background: The poignant part of the problem is that these are mostly preventable. The word poison originates from the latin word potionem which means deadly draught. The Herald of modern Toxicology, Paracelsus, supposed that everything is poison and only the dose plays a pivotal role. Objective: The aim of the study to investigated the demographical, etiological and clinical characteristics of acute drug poisonings. Methodology: The study design was descriptive observational type of case study that was conducted in different public and private hospital in Dhaka city. A sample of 100 poisonings patients was taken by convenience sampling technique. The selection of cases was based on the patient's diagnosis on discharge and was accomplished through analysis of all the medical records of the patients hospitalized in Internal Medicine and Toxicology Department, from the Jan. 2017 to Dec. 2018. Results: Acute drug poisonings incidence rate was 25.6%, majority (69.0%) patients were female. Majority (36.0%) of the patients were multiple drug poisonings followed by 14(14.0%) were benzodiazepines, 9(9.0%) anticonvulsants, 9(9.0%) barbiturates and 6(6.0%) cardiovascular medication. Category of acute drug poisonings were not statistically significant (p>0.05) between male and female groups. Conclusion: Female were predominant and majority of them were multiple drug poisonings. Common drug poisonings were found benzodiazepines, anticonvulsants, barbiturates and cardiovascular medication. J.Dhaka National Med. Coll. Hos. 2019; 25 (01): 11-15